Analysis of Labor Needs at Perawang Port 2013 - 2018 - Royandi; Harlen; Any Widayatsari (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2020)
Shipment of container has become a phenomenon in the world of logistics it is seen as more efficient and effective means of transportation. Changes in shipment patterns from break bulk cargo to containers also occur in the port of Perawang along with the construction of bridges in Siak Sri Indrapura so that large vessels can no longer enter and carry out loading and unloading activities at the Perawang port, and this has resulted in companies having to invest in mechanical equipment because ships that enters the perawang private jetty is no longer supported by the crane on the ship. Based on data owned by PT. Indah Kiat Perawang container shipments continue to increase from year to year but not accompanied by an increase in the number of labor. This study aims to see the effect of Container Shipment, Mechanical Equipment Investment and Labor Wages on Labor Demand at perawang port. This study uses secondary data with data from 12 semesters from 2013 to 2018. With independent variables namely Container Shipment, Investment and Wages. The analysis technique used is multiple regression. The results of the research shows that container shipment and investment has no significant effect on labor demand, whilts wages has a significant and negative effect on labor demand